2013
DOI: 10.1021/jm301899y
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design and Evaluation of Naphthalene Diimide G-Quadruplex Ligands As Telomere Targeting Agents in Pancreatic Cancer Cells

Abstract: Tetra-substituted naphthalene diimide (ND) derivatives with positively charged termini are potent stabilizers of human telomeric and gene promoter DNA quadruplexes and inhibit the growth of human cancer cells in vitro and in vivo. The present study reports the enhancement of the pharmacological properties of earlier ND compounds using structure-based design. Crystal structures of three complexes with human telomeric intramolecular quadruplexes demonstrate that two of the four strongly basic N-methyl-piperazine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
167
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(176 citation statements)
references
References 86 publications
6
167
0
Order By: Relevance
“…One such compound (MM41: Fig. 1) has been characterised as a potent stabiliser of various quadruplex sequences and inhibitor of cell growth in a panel of cancer cell lines28. In particular it shows selectivity for several pancreatic cancer lines and its IC 50 value (the concentration required to inhibit cell growth by 50% in a 96 hr assay), is 10 nM in the MIA PaCa-2 pancreatic adenocarcinoma cell line.…”
mentioning
confidence: 99%
“…One such compound (MM41: Fig. 1) has been characterised as a potent stabiliser of various quadruplex sequences and inhibitor of cell growth in a panel of cancer cell lines28. In particular it shows selectivity for several pancreatic cancer lines and its IC 50 value (the concentration required to inhibit cell growth by 50% in a 96 hr assay), is 10 nM in the MIA PaCa-2 pancreatic adenocarcinoma cell line.…”
mentioning
confidence: 99%
“…31 MMQ1 quinacridine-based ligand was described as an anti-cancer agent in 2007 by Hounsou et al 32 The G-quadruplex stabilising properties of the MMQ1 series were confirmed by Hou et al 33 and Gabelica et al 34 MM41 is a tetra-substituted naphthalenediimide derivative described first by Micco et al 35 as a potent stabilizer of human telomeric and gene promoter DNA quadruplexes and can inhibit the growth of human cancer cells in vitro and in vivo. Recently, Ohnmacht et al reported MM41's significant in vivo anti-tumour activity against the MIA PaCa-2 pancreatic cancer xenograft model.…”
Section: Review Articlementioning
confidence: 98%
“…For example, Fig. 3 presents interactions of small molecules with target genes and by molecular simulation technique [15,16]. …”
Section: A Interactions Between Target Genes and Smallmentioning
confidence: 99%